2009
DOI: 10.1007/s11483-009-9129-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Vitamin E and Trolox: Understanding of the Factors that Govern Lipid Peroxidation Studies In Vitro

Abstract: Peroxidation of lipids is of significant interest owing to the evidence that peroxyl radicals and products of lipid peroxidation may be involved in the toxicity of compounds initiating a deteriorative reaction in the processing and storage of lipid-containing foods. In view of the significance of the antioxidant role of the dietary compound vitamin E and its water-soluble analogue Trolox in research of lipid-containing foods, it is desirable to determine more specifically how and where they operate its antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 34 publications
1
70
0
1
Order By: Relevance
“…Trolox lacks the long fatty acid chain but has the same chroman ring structure, reduction activity and membrane stabilizing potential. Trolox can donate hydrogen from the hydroxyl group to the peroxyl radical converting it into a lipid hydroperoxide and a Trolox phenoxyl radical thus terminating the chain reaction [34,35]. Similar as in other in vitro studies [36], Trolox could also reduce ferryl Hb back to ferric Hb, thereby providing a way for the decay of this highly oxidant species.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Trolox lacks the long fatty acid chain but has the same chroman ring structure, reduction activity and membrane stabilizing potential. Trolox can donate hydrogen from the hydroxyl group to the peroxyl radical converting it into a lipid hydroperoxide and a Trolox phenoxyl radical thus terminating the chain reaction [34,35]. Similar as in other in vitro studies [36], Trolox could also reduce ferryl Hb back to ferric Hb, thereby providing a way for the decay of this highly oxidant species.…”
Section: Discussionmentioning
confidence: 63%
“…Similar to α-tocopherol, Trolox is primarily a chainbreaking antioxidant. Its antioxidant activity is related to the structural characteristics and the ability to interact with/penetrate the lipid bilayers [34]. Due to the hydrophobic nature α-tocopherol distributes totally in the membranes restricting the mobility of their components.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we focused on vitamin E, which is an antioxidant known to prevent metastasis and DNA damage in cancer cells (29). Instead of using vitamin E directly, we used Trolox, which is a water soluble derivative of vitamin E, because of the hydrophobicity of vitamin E (16). In this study, we used PMA to increase expression of both MMP-2 and -9, as described in a previous study (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, vitamin E is an extremely hydrophobic antioxidant in a buffered solution, and its antioxidant activity is not always consistent in experimental models (16). The antioxidant 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox) is a water-soluble derivative of vitamin E that can be studied in an intact system (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…There are several molecular features that govern the behavior of a drug in cell membranes such as size, shape, solubility, hydrophilicity, lipophilicity, and pK a , among others. Previously, many authors have reported studies of the interaction of drugs and membrane models with experimental technics (Nunes et al 2011;Lucio et al 2009;Fuchs et al 1990) and molecular dynamic (MD) simulations (Robinson et al 1995;Gabdouline et al 1996;Smondyrev andBerkowitz 1999, 2001;Hofsäß et al 2003;Pereira et al 2004;Falck et al 2006;Högberg et al 2007;Seddon et al 2009;Sirk et al 2009;Boggara and Krishnamoorti 2010;Witzke et al 2010;Orsi andEssex 2010, Koukoulitsa et al 2011;Nitschke et al 2012;Poger and Mark 2013;Loverde 2014;Jalili and Saeedi 2016). In particular, studies based on drug partitioning in lipid bilayers and the thermodynamics of drug/lipid interaction have great importance in understanding the reaction mechanisms of antitumor drugs and to design new cell membrane-targeted drugs (Boggara and Krishnamoorti 2010;Jendrossek and Handrick 2003;Goldstein et al 2011;Choi et al 2013).…”
Section: Introductionmentioning
confidence: 99%